Synopsis: Study of the determinants of chronic malnutrition in northern Nigeria: Quantitative evidence from the Nigeria Demographic and Health Surveys - Amare, Mulubrhan; Benson, Todd; Fadare, Olusegun; Oyeyemi, Motunrayo (International Food Policy Research Institute, 2017)
To better understand the drivers of chronic child undernutrition in northern Nigeria and how those drivers differ from those in other areas of the country, an econometric analysis was done of data from the 2008 and 2013 Nigeria Demographic and Health Surveys (NDHS). The analyses focused on children aged 6 to 23 months.